Avaliação de maracujazeiros em condições de clima temperado: produção, qualidade e compostos bioativos - Weber, Diego (2016)
The fruticulture is an important activity in Brazil and is very adapted to family farming and the proposed diversification of small areas of production. The passion fruit (Passifloras) are plants that play an important role for many family farmers due to high demand of manpower and considerable income for small farms. In Brazil, the cultivated species featured include the yellow passion fruit (Passiflora edulis Sims.), the purple passion fruit (Passiflora edulis Sims.) and sweet passion fruit (Passiflora alata Curtis.). With edaphoclimatic adaptability cultural diversity of Brazil, it is possible the yellow passion fruit production in all regions of the country. However, for a better understanding, it is necessary to further studies in different locations from those of commercial cultivation. Soil and climatic conditions of southern Rio Grande do Sul (State of Brazil), has some specific soil and climate in relation to the tropical regions of traditional cultivation. So, to that the growers can diversify their production with passion fruit, it is necessary studies to adapt the genotypes already on the market, for a new location. Therefore, this work aimed to evaluate productive aspects, the physicochemical quality and bioactive compounds from juice, flour from the peel and leaves of the genotypes of commercial passionfruit grown in Pelotas, Brazil. The thesis comprises three articles and were developed in UFPel/FAEM, between the years 2013 and 2015. The Article 1 was titled production and fruit quality of passion fruit in temperate conditions. Were evaluated genotypes: Passiflora edulis ‘Catarina’; Passiflora edulis ‘BRS Sol do Cerrado’ e, Passiflora edulis ‘BRS Rubi do Cerrado’. All genotypes showed potential for production in the region of Pelotas, RS. The physicochemical quality of the fruits of genotypes are within acceptable parameters.The Article 2 was titled bioactive compounds from leaves, peel and juice of genotypes of passion fruit. Were evaluated genotypes: ‘Catarina Roxo’ (Epagri); ‘Catarina’ (Epagri); ‘Urussanga’ (Epagri); ‘BRS Gigante Amarelo’; ‘BRS Rubi do Cerrado’; ‘BRS Sol do Cerrado’. For evaluations of leaves ‘BRS Gigante Amarelo’ genotype was not evaluated. There were differences among genotypes for all bioactive compounds evaluated. It can be concluded that the genotypes of passion fruit evaluated in this study, have potential as a source of bioactive compounds. The Article 3 was entitled production and fruit quality of sweet passion fruit selection ‘Urussanga’ in temperate climate. The genotype characterized was selection Urussanga selected by Epagri, derived from sweet passion fruit (Passiflora alata Curtis.). Overall the sweet passion fruit selection Urussanga, shows productive potential and fruit physicochemical quality adequate when grown in temperate conditions. However, based on the results obtained and discussed in this thesis, it can be concluded that the production, quality and bioactive compounds of genotypes evaluated passionfruit can be commercially exploited by producers who wish to diversify production in non-traditional area of cultivation. It is concluded that this thesis comply with the initial justification, which therefore proves the existence of potential for passion fruit production in temperate climate conditions.